2018
DOI: 10.1080/09581596.2018.1516034
|View full text |Cite
|
Sign up to set email alerts
|

The Commission on Social Determinants of Health: Ten years on, a tale of a sinking stone, or of promise yet unrealised?

Abstract: Ten years after the August 2008 release of the report of the WHO Commission on Social Determinants of Health, it is important to reflect on the fate of its recommendations for reducing 'health inequity'. The article describes some key developments in the decade, notably in understanding the etiology of health inequalities, and then juxtaposes a hopeful comparison of an earlier (1987) UN Commission on Environment and Development with a sceptical view based on the expanding social science literature on the polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…For example, we heed John Frank and colleagues' call for rethinking the social determinants of health because, among other reasons, the complexities of globalisation and its attendant politics make the time 'ripe for significant evolution' into more nuanced and politically attuned framings (Frank et al, 2020: 1). And we agree with Schrecker (2019) when he claims there has been a failure 'at the crucial level of national politics' of policies at any level to decrease inequities during a historical moment of increasing global inequalities. COVID-19 indeed has shown that the neoliberal tendency to address harm only when there are crises and disasters, and to divest from programmes that might eradicate some of the root causes of unequal burdens of disease such as reduction of public investment, privatisation of healthcare and impoverishment of public health infrastructures (Navarro, 2007(Navarro, , 2020, becomes quite literally murderous to millions.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…For example, we heed John Frank and colleagues' call for rethinking the social determinants of health because, among other reasons, the complexities of globalisation and its attendant politics make the time 'ripe for significant evolution' into more nuanced and politically attuned framings (Frank et al, 2020: 1). And we agree with Schrecker (2019) when he claims there has been a failure 'at the crucial level of national politics' of policies at any level to decrease inequities during a historical moment of increasing global inequalities. COVID-19 indeed has shown that the neoliberal tendency to address harm only when there are crises and disasters, and to divest from programmes that might eradicate some of the root causes of unequal burdens of disease such as reduction of public investment, privatisation of healthcare and impoverishment of public health infrastructures (Navarro, 2007(Navarro, , 2020, becomes quite literally murderous to millions.…”
Section: Introductionsupporting
confidence: 67%
“…Finally, we do not pretend that this framework will make easy the changes we firmly believe need to happen if communities are going to be stronger in their everyday as well as pandemic contexts. The website of the People’s Health Movement (phmovement.org/global-health-watch-5th-edition) – a Global South-based organisation of physicians and activists – echoes what many others have said (see Frank et al, 2020; Schrecker, 2019) in bemoaning the ‘inability of the current neoliberal order to address the rising crisis in health’ where ‘governance for health is being held captive by private foundations and corporations’. Seeking radical change in the face of such powerful forces entrenching the status quo of extreme inequity is not easy, but we don’t find this an adequate argument for abandoning the goal of health equity and pandemic prevention.…”
Section: Introductionmentioning
confidence: 97%
“…The role of circumstances beyond an individual’s control must be emphasized, rather than deficits in personal resilience. In suggesting this, we acknowledge the work of those concerned with inequalities in health more broadly, in continuing to pursue this agenda, albeit in an unreceptive political climate (see, e.g., Stevens 2011; Donkin et al 2017; Schrecker 2019).…”
Section: Obesity As a Response To Stressful Circumstancesmentioning
confidence: 99%
“…However, many prominent observers have judged "the health gap" across social classes not to be closing in most societies over the last decade [4][5][6][7]. Strikingly, despite this negative finding, few researchers-McQueen, Crammond and Carey, and Schrecker being notable exceptions [8][9][10]-appear to have seriously questioned the conceptual SDoH framework itself.…”
Section: Purpose/rationalementioning
confidence: 99%
“…Schrecker [10], writing a decade after McQueen, calls attention to the "hard (difficult) politics of inequality," which he blames for much of the apparent ineffectiveness of policies in several countries which have at least tried to reduce socioeconomic inequalities and related health disparities. He is particularly convincing on the role of international trade agreements in maintaining both economic and health inequalities, combined with transnational corporations' normal operating methods-including shifting profits/jobs to lower-tax/pay settings, aided and abetted by the shadowy world of global tax shelters.…”
mentioning
confidence: 99%